2015
DOI: 10.1111/jnc.13246
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene‐related peptide erases the fear memory and facilitates long‐term potentiation in the central nucleus of the amygdala in rats

Abstract: Calcitonin gene-related peptide (CGRP) is a 37 amino acid neuropeptide, which plays a critical role in the central nervous system. CGRP binds to G protein-coupled receptors, including CGRP1, which couples positively to adenylyl cyclase (AC) and protein kinase A (PKA) activation. CGRP and CGRP1 receptors are enriched in central nucleus of the amygdala (CeA), the main part of the amygdala, which regulates conditioned fear memories. Here, we reported the importance of CGRP and CGRP1 receptor for synaptic plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…22 (recording at 31℃), by Wu et al. 23 (at room temperature), and in this study (at room temperature) would suggest that the lower temperature used in this study and that by Wu et al. 23 would not resulted in the absence of this CGRP effect.…”
Section: Discussionsupporting
confidence: 50%
“…22 (recording at 31℃), by Wu et al. 23 (at room temperature), and in this study (at room temperature) would suggest that the lower temperature used in this study and that by Wu et al. 23 would not resulted in the absence of this CGRP effect.…”
Section: Discussionsupporting
confidence: 50%
“…We hypothesized that the release of stored calcium by ryanodine may selectively stimulate the exocytosis of CGRP‐containing LDCVs, which will be followed by the increase in MEPP amplitude as the result of activation of CGRP receptors by released endogenous CGRP. To test this hypothesis, we studied the action of 0.1 μM of ryanodine in the presence of truncated CGRP (CGRP 8‐37 , 1 μM) which is widely used as CGRP‐receptor blocker (Gaydukov et al., 2016; Han, Adwanikar, Li, Ji, & Neugebauer, 2010; Hay, Garelja, Poyner, & Walker, 2017; Wu et al., 2015). We have shown that CGRP 8‐37 alone had no significant effect on MEPP amplitude (Gaydukov et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…CGRP was also reported to attenuate learning impairments induced by the NMDA receptor antagonist dizocilpine (8). More recently, however, Wu et al reported the CGRP-induced extinction of fear memory in the central nucleus of the amygdala in rats (9). Thus, several studies have reported that CGRP might affect memory formation, but the results have been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP was found to attenuate the learning impairments induced by dizocilpine, an N-methyl-D-aspartate (NMDA) receptor antagonist, as assessed using a step-down, passive avoidance task (8). In contrast with these findings, more recently, Wu et al reported that CGRP induced the extinction of fear memories in the central nucleus of the amygdala in rats (9). Thus, CGRP may modulate fear memory processing; however, whether CGRP enhances fear memory retention and what signaling mechanisms it acts through remain unclear.…”
Section: Introductionmentioning
confidence: 96%